2017
DOI: 10.1073/pnas.1703477114
|View full text |Cite
|
Sign up to set email alerts
|

Social propinquity in rodents as measured by tube cooccupancy differs between inbred and outbred genotypes

Abstract: Existing assays of social interaction are suboptimal, and none measures propinquity, the tendency of rodents to maintain close physical proximity. These assays are ubiquitously performed using inbred mouse strains and mutations placed on inbred genetic backgrounds. We developed the automatable tube cooccupancy test (TCOT) based on propinquity, the tendency of freely mobile rodents to maintain close physical proximity, and assessed TCOT behavior on a variety of genotypes and social and environmental conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…The current observations replicate the main finding of our previous study, that in the absence of pain, outbred CD‐1 mice of both sexes show higher levels of propinquity (tube co‐occupancy) if they are familiars than if they are strangers (compare sibling‐NP and stranger‐NP groups in Figure ). The main purpose of the current study was to investigate how the presence of pain might affect this sibling vs stranger difference in social behavior.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The current observations replicate the main finding of our previous study, that in the absence of pain, outbred CD‐1 mice of both sexes show higher levels of propinquity (tube co‐occupancy) if they are familiars than if they are strangers (compare sibling‐NP and stranger‐NP groups in Figure ). The main purpose of the current study was to investigate how the presence of pain might affect this sibling vs stranger difference in social behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Mice in the dyad were in one of two social relation conditions: (1) sibling (born of the same parents and raised together in a single home cage from birth until weaning, and in a single home cage with same‐sex littermates from weaning until testing), or (2) stranger (born of different parents with no contact prior to testing). We previously showed that TCOT behavior is identical when mice are familiar and related compared with mice that are familiar and nonrelated, and for ethical reasons chose to test only siblings. Sibling and stranger mice were randomly assigned to one of three pain conditions: (1) no pain (NP; in which neither mouse in the dyad received any noxious stimulus), (2) one‐in‐pain (OP; in which one mouse of the dyad received the noxious stimulus but the other did not), or (3) both‐in‐pain (BP; in which both mice in the dyad received the same noxious stimulus).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations